Determination of the Chemical Properties of Some Selected Vegetable Oils Sold in Gombe Main Market, Gombe State, Nigeria - Lazarus Joseph Goje; Muhammad Auwal Muhammad; Fatima Umar Maigari; Abubakar Muhammad Hammari (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Vegetable oils are widely utilized as essential lipid sources in food production, necessitating routine evaluation of their nutritional and chemical quality. This study assessed the quality of four commonly consumed edible vegetable oil brands in Gombe, Gombe State: Palm oil (Al-Hilal), Turkey oil, Power oil, and Kings oil. Samples were collected from the Gombe main market and analyzed for saponification value, iodine value, and peroxide value. These parameters were compared against the standards set by the Standard Organization of Nigeria (SON). Turkey oil exhibited the lowest saponification value (192.43 ± 0.51 mg KOH/g), though all oils fell within the SON-recommended range of 185–205 mg KOH/g. The iodine values indicated low levels of unsaturated fatty acids across all samples, with palm oil showing the highest (15.29 ± 0.49 g) and Turkey oil the lowest (6.61 ± 0.63 g). Peroxide values for all samples were well below the 10 meq/kg threshold for rancidity, indicating freshness and stability. Overall, the results demonstrate that all vegetable oil samples met the quality standards set by SON and the Nigerian Industrial Standard (NIS). It is therefore concluded that the oils are unadulterated, of high quality, and safe for public consumption, reflecting proper processing and storage practices.